Therapy for Recurrent High-Grade Epithelial Ovarian Cancer—The Current Status and Future Trends - Vallathol Dilip Harindran; V.P. Sanudev Sadanandan; P. Vishnu Sreedath; Parameswaran Prashanth; K.V. Sajeevan; P.S. Sreedharan; Narayanankutty Warrier (Indian Journal of Medical and Paediatric Oncology)
Ovarian malignancy is the seventh most frequently diagnosed cancer among women. The most common type is epithelial ovarian cancer. Several subtypes with distinct biological and molecular properties exist, and there is inconsistency in availability of and access to different modalities of treatment. The standard first-line management is combining surgery and platinum-based chemotherapy. Most of them are diagnosed at an advanced stage due to which they have poor outcomes. The existing screening tests have a low predictive value. Even with the best available upfront treatment, high rates of recurrences are observed. As a result, there have been major advances in the treatment of recurrences with the development of anti-angiogenic agents and PARP inhibitors. It has led to the improvement in survival and quality of life among the relapsed epithelial ovarian cancers. This review is focused on the management of recurrent epithelial ovarian cancers and future directions based on current evidence. The application of a personalized and structured approach will meaningfully bring changes in the paradigm of care in these groups of patients.